Hospital Episode Statistics and trends in ophthalmic surgery 1998 – 2004 - Fraser Scott G; Clarke Lucy C (BMC Ophthalmology, 2006)
Abstract Background Hospital episode statistics (HES) is a UK national database for the National Health Service (NHS), now available online. The purpose of this study was to observe trends in ophthalmic operations performed during the period from 1998 to 2004, using this data. Methods From the 'Main Operation' codes within the 'Free data' section of the HES website we analysed data in regard to 28 specific ophthalmic operations. These represented each sub speciality within ophthalmology. Results The figures show a change in the total number and proportions of operations performed for many of the procedures. For example, there was an increase in numbers of orbital decompressions, but a decrease in numbers of glaucoma filtering operations. Changing trends could be seen in different surgical areas such as the change in operations used for corneal grafting and in retinal surgery. Conclusion The HES database represents an important, potentially useful source of information. There are imitations in interpretation of and validity of such data related to coding inconsistencies. We suggest the benefit of the data comes from observing trends rather than exact numbers. As other studies using this data have suggested, it is important that clinicians are involved in improving the quality of this data.